Azaindole derivatives are inhibitors of microtubule dynamics, with anti‐cancer and anti‐angiogenic activities. (16th January 2013) - Prudent, Renaud; Vassal‐Stermann, Émilie; Nguyen, Chi‐Hung; Mollaret, Marjorie; Viallet, Jean; Desroches‐Castan, Agnès; Martinez, Anne; Barette, Caroline; Pillet, Catherine; Valdameri, Glaucio; Soleilhac, Emmanuelle; Di Pietro, Attilio; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose Drugs targeting microtubules are commonly used for cancer treatment. However, the potency of microtubule inhibitors used clinically is limited by the emergence of resistance. We thus designed a strategy to find new cell‐permeable microtubule‐targeting agents. Experimental Approach Using a cell‐based assay designed to probe for microtubule polymerization status, we screened a chemical library and identified two azaindole derivatives, CM01 and CM02, as cell‐permeable microtubule‐depolymerizing agents. The mechanism of the anti‐tumour effects of these two compounds was further investigated both in vivo and in vitro. Key Results CM01 and CM02 induced G2/M cell cycle arrest and exerted potent cytostatic effects on several cancer cell lines including multidrug‐resistant (MDR) cell lines. In vitro experiments revealed that the azaindole derivatives inhibited tubulin polymerization and competed with colchicines for this effect, strongly indicating that tubulin is the cellular target of these azaindole derivatives. In vivo experiments, using a chicken chorioallantoic xenograft tumour assay, established that these compounds exert a potent anti‐tumour effect. Furthermore, an assay probing the growth of vessels out of endothelial cell spheroids showed that CM01 and CM02 exert anti‐angiogenic activities. Conclusions and Implications CM01 and CM02 are reversible microtubule‐depolymerizing agents that exert potent cytostatic effects on human cancer cells of diverse origins, including MDR cells. They were also shown to inhibit angiogenesis and tumour growth in chorioallantoic breast cancer xenografts. Hence, these azaindole derivatives are attractive candidates for further preclinical investigations.